The relationship between the extent of TQM practices and the importance on business performance: a survey in Malaysia - Ahmad, Md Fauzi (2013)
In today’s highly competitive market, business performance is one of the critical factors for companies to survive in the global marketplace. The concept of total quality management (TQM) has been developed as a result of intense global competition for improving business performance. Many previous studies discussed about TQM and the extent of the TQM practices, however, almost previous works were given less emphasis on the relationships between the extent of TQM factors and it's importance to business performance based on the individual factors in TQM, which is identified as theoretical gap. The main contribution of this study is to identify the most effective TQM factors based on the level of practices and it's importance to the business performance. A questionnaire was prepared and sent to 1500 companies from the automotive industry in Malaysia which gave a 21.9% response rate or 319 respondents. This study reveals that perception of ranking based on the practices is different compared to ranking based on it's importance to business performance. Furthermore, Kendall tau correlation test for rank analysis shows that correlation coeffient. r is -0.333 between rank of practices and its importance. It means that higher extent of TQM practices has less importance with business performance. Thus, the final ranking is finalized based on the practices level and it's importance to business performance as follows; (1)Management strategy and policy; (2)Customer focus; (3)Continuous improvement; (4)Supplier management; (5)Work process; (6)Business ethics; (7)Top management leadership; (8)Information and analysis; (9)Human resource development; (10) New product management. This research will help the academicians and industry players to have better understanding on the importance of TQM practices in effective way to the company in improving business performance.